Translocating shRNA: a novel approach to RNA interference with Newcastle disease virus as viral vector - Koh, Wei Chin; Yusoff, Khatijah; Song, Adelene Ai Lian; Saad, Norazalina; Tan, Tiong Kit; Cheow, Pheik Sheen; Chia, Suet Lin (Microbiology Society, 2025)
RNA interference is crucial in post-transcriptional gene silencing. Short hairpin RNA (shRNA) is particularly effective because it forms fully complementary matches with target mRNA, leading to its degradation. However, shRNA processing relies on nuclear microprocessors like Drosha, posing a challenge for RNA viral vectors that replicate exclusively in the cytoplasm. Although there have been reports of Drosha translocating to the cytoplasm upon viral infection, many RNA viruses, including Newcastle disease virus (NDV), remain inadequately studied in this context and, in some cases, fail to induce Drosha translocation for shRNA processing. In this study, we developed a novel approach to translocate an shRNA, expressed by NDV as an RNA viral vector, into the nucleus for Drosha processing. As a proof of concept, a recombinant NDV expressing the shRNA (rAF-shmcherry) with an AU-rich region at its 3′ end in the expression cassette was constructed. This shRNA targets a constitutively expressed mCherry gene in a colorectal cancer cell line, SW620-mC. We confirmed the presence of the AU-rich shRNA in the nuclei of the rAF-shmcherry-infected SW620-mC using reverse transcription PCR (RT-PCR). The gene-silencing effect of the shRNA was then evaluated at mRNA and protein levels, showing ~90% downregulation of the mCherry transgene at 24 h post-infection and 70% downregulation of mCherry protein in SW620-mC at 48 h post-infection. This study marks the first exploration of NDV as an shRNA viral vector, presenting a promising approach for shRNA translocation that could be applicable to various RNA viruses.